Ecological aspects of the substrate and water relations of deciduous and evergreen plant forms in the western Karoo - Midgley, Guy F (Department of Biological Sciences, 2016)
The principle aim of this work was to ascertain the relative importance of water and nutrient supply in determining the success of deciduous and evergreen plant forms on two main substrate types in the Worcester-Robertson valley, situated in the Succulent Karoo Biome. The substrate types selected for study represent soils of zoogenic soil mounds (locally termed "heuweltjies", and often referred to in the literature as "Mirna-like" mounds), and soils immediately adjacent to and surrounding the soil mounds. The distribution of deciduous and evergreen plant forms in the Worcester-Robertson valley was analys~d relative to the selected substrate types. Foliar elemental concentrations of four selected species growing on both substrates at five separate sites within the valley were determined. Also, the patterns of seasonal water stress exhibited by three deciduous and five evergreen non-succulent woody perennials growing in both substrates were investigated on high radiation (equator-facing) and low radiation (pole-facing) slopes at one intensive study site, the Worcester Veld Reserve.